THE INFLUENCE OF BRAND IMAGE ON SATISFACTION TO IMPROVE CUSTOMER RETENTION TOWARDS BATIK KERIS IN MALANG CITY - Puspaningrum, Astrid (Jurnal Aplikasi Manajemen, 2020)
The purpose of this study is to analyze the role of customer satisfaction as a mediator of the influence of brand image on customer retention of Batik Keris in Malang. The approach used in this research was positivism (quantitative). The population of this study was the customers of Batik Keris in Malang City, with a total sample of 50 customers in Malang City. The data obtained were analyzed using Path Analysis. The results showed that brand image directly affects the customer satisfaction of Batik Keris. Customer satisfaction directly affects customer retention of Batik Keris, and customer satisfaction mediates the influence of brand image and customer retention towards Batik Keris. Therefore, customer retention will be high if the brand image that is highlighted by Batik Keris can satisfy the customers.